The occurrence of the hover fly genus Eristalis Latreille, 1804 (Diptera: Syrphidae) in the Afrotropical region - De Meyer, M.; Goergen, G.; Bellingan, T.; Midgley, J.; Jordaens, K. (2025)
The Afrotropical hover flies placed in the genus Eristalis Latreille, 1804 (Diptera: Syrphidae) are revised and the taxonomic history of the placement, and identity, of the different species is presented. Five species are recognised, of which only three can be clearly defined: E. pallidibasis (Bigot, 1891), E. plumipes Bezzi ,1912, and E. tenax (Linnaeus, 1758). Eristalis apis Curran, 1939 syn. nov. is proposed as a junior synonym of E. pallidibasis (Bigot, 1891). Eristalis convexifacies Macquart, 1850 is known only from a badly damaged holotype. The identity of Simoides trichopus Bigot, 1891, (now considered to be an Eristalis) is uncertain as its type material could not be traced and the original description lacks sufficient detail. For the time being, S. trichopus is considered a nomen dubium. An identification key and detailed redescriptions are provided. Eristalis pallidibasis, E. plumipes and E. tenax are easily identified using DNA barcoding. The relationship of Afrotropical Eristalis with Afrotropical representatives of other eristaline genera is briefly discussed based on morphological data.